FOUNDATION OF PSYCHOLOGICAL TESTING : A PRACTICAL APPROACH - LESLIE A. MILLER; SANDRA A. MCLNTIRE, ROBERT L. LOVLER (SAGE PUBLICATION, CALIFORNIA, 2011)
This third edition of this text offers a straightforward presentation on the basics of psychological testing as well as on psychometrics and statistics for students new to the field. Primarily concerned with preparing students to become informed consumers and users of tests, this user friendly text also features a section focusing on how tests are utilized in three important setting: education, clinical and counselling practice, and organizations.
Keywords: Psychological Testing